Participatory action research in corrections: The HITEC 2 program. (March 2016) - Cherniack, Martin; Dussetschleger, Jeffrey; Dugan, Alicia; Farr, Dana; Namazi, Sara; El Ghaziri, Mazen; Henning, Robert
Abstract: Background: HITEC 2 (Health Improvement through Employee Control 2) is the follow-up to HITEC, a participatory action research (PAR) program that integrates health and work conditions interventions designed by the workforce. HITEC 2 compares intervention programs between two correctional sites, one using a pure workforce level design team and the other using a more structured and time delineated labor-management kaizen effectiveness team. Methods: HITEC 2 utilizes a seven step participatory Intervention Design and Analysis Scorecard (IDEAS) for planning interventions. Consistent with PAR, process and intervention efficacy measures are developed and administered through workforce representation. Results: Participation levels, robustness of participatory structures and sophistication of interventions have increased at each measured interval. Health comparisons between 2008 and 2013 showed increased hypertension, static weight maintenance, and increased 'readiness to change'. Conclusions: The PAR approaches are robust and sustained. Their long-term effectiveness in this population is not yet clear. Highlights: A participatory action research project implemented with correctional officers is described. We examine 2 different participatory approaches that use the IDEAS tool. Outcomes are varied based on intervention theme and implementation.